Mutu bubuk bawang putih berdasarkan sifat fisiko-kimia dan preferensi konsumen - Kendri Wahyuningsih; Kirana Sanggrami Sasmitaloka (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Currently, consumers are more interested in using herbs and spices in powder form because of their practicality. One of them is garlic powder, which has been circulating commercially. However, this commercial product has been found on the market in various quality classes, and it is suspected that there is potential for counterfeiting. Therefore, it is necessary to identify the quality of commercial garlic powder. The aim of this study is to determine the quality of commercial garlic powder based on its physicochemical properties and the level of consumer preference. In the primarily stage, commercial garlic powder sampling was carried out, namely bulk-quality samples from traditional markets and export-quality samples from modern markets. The selection of garlic powder products represents two consumer segments: heterogeneous consumers, represented by bulk-quality garlic powder, and homogeneous consumers, represented by export-quality garlic powder. Native garlic powder was prepared in the laboratory by slicing, drying (temperature 40-50C), and milling methods. Quality analysis has been carried out on physico-chemical properties, and sensory tests have been performed to determine the level of consumer preference. Commercial garlic powder has a different morphological structure compared to native garlic powder. Meanwhile, the color and allicin content of commercial bulk-quality garlic powder are significantly different compared to native garlic powder. Meanwhile, consumers tend to prefer commercial garlic powder in terms of color, aroma, and texture.